2018
DOI: 10.2169/internalmedicine.0225-17
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics, Phenotype of Lipodystrophy and a Genetic Analysis of Six Diabetic Japanese Women with Familial Partial Lipodystrophy in a Diabetic Outpatient Clinic

Abstract: Objective Our aim was to examine the clinical characteristics and phenotype of lipodystrophy of six diabetic Japanese women with partial lipodystrophy (PL) who received a genetic analysis at a diabetic outpatient clinic. Methods We screened for PL using dual energy X-ray absorptiometry (DEXA) and magnetic resonance imaging (MRI) among patients who had a reduced peripheral skinfold thickness at the diabetic outpatient clinic of Kusatsu General Hospital between August 2003 and August 2013. We performed a mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…Previous studies reported that patients with FPLD1 may be predisposed to the development of severe atherosclerosis ( 8 , 10 , 12 , 13 ). Atherosclerosis has been considered to be caused by the accumulation of atherogenic risk factors, such as diabetes, dyslipidemia, hypertension, and low levels of serum adiponectin in patients with FPLD1.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies reported that patients with FPLD1 may be predisposed to the development of severe atherosclerosis ( 8 , 10 , 12 , 13 ). Atherosclerosis has been considered to be caused by the accumulation of atherogenic risk factors, such as diabetes, dyslipidemia, hypertension, and low levels of serum adiponectin in patients with FPLD1.…”
Section: Discussionmentioning
confidence: 99%
“…The heterozygous variant p.R4810K in mysterin is found at a rate of >90% in Japanese patients with MMD (1). However, due to low genetic penetrance, carriers of this variant do not always develop MMD (1, 4); therefore, additional environmental and/or genetic factors are considered to be important for the development of MMD in Previous studies reported that patients with FPLD1 may be predisposed to the development of severe atherosclerosis (8,10,12,13). Atherosclerosis has been considered to be caused by the accumulation of atherogenic risk factors, such as diabetes, dyslipidemia, hypertension, and low levels of serum adiponectin in patients with FPLD1.…”
Section: A B C D E F Discussionmentioning
confidence: 99%
See 3 more Smart Citations